Detection of Borrelia in the synovial tissue from a patient with Lyme borreliosis by electron microscopy - Valesová, M; Trnavský, K; Hulínská, D; Alusík, S; Janousek, J; Jirous, J (The Journal of rheumatology, 1989)
We describe a woman who suffered for several years from joint pain with subsequent development of arthritis of her left knee. Because of these symptoms she was subjected to repeated studies including arthroscopy and menisectomy. IgG antibodies to Borrelia determined by ELISA were reported to be present and showed an increase of IgG titer to 1:1024. Histology from the last synovial biopsy disclosed only evidence of a nonspecific synovitis and marked inflammatory infiltration with lymphocytes and plasma cells. Borrelia-like structures were detected electron microscopically on semithin Epon sections from the lumen of the strongly infiltrated blood capillary. In our case the detection of Borrelia indicated the basis for increase of antibodies against Borreliae. It established the correct diagnosis and led to specific therapy of the disease after several years of unsuccessful attempts to control it.
Keywords: recidiva; Humans; lidé středního věku; Borrelia burgdorferi Group; imunoglobulin G; Synovitis; Lyme Disease; lymeská nemoc; Female; protilátky bakteriální; lidé; synovitida; Synovial Membrane; Antibodies, Bacterial; ženské pohlaví; synoviální membrána; Borrelia burgdorferi komplex; Middle Aged; Recurrence; Immunoglobulin G